الاستثمار السياحي في مدينة عدن بين المعوقات ومتطلبات تحسين مناخ الاستثمار - محفوظ, ابتهال (University of Eloued جامعة الوادي, 2022)
هدفت هذه الدراسة إلى دراسة وتحليل الاستثمار السياحي ومساهمته في اجمالي الاستثمار مقارنةً بالقطاعات الأخرى في مدينة عدن خلال الفترة 2001-2020, بالإضافة إلى الكشف عن المعوقات التي تواجه الاستثمار السياحي, ووضع قائمة مقترحة لاهم المتطلبات لتحسين مناخ الاستثمار السياحي, ولتحقيق أهداف البحث تم استخدام المنهج الوصفي التحليلي. وقد توصلت الدراسة إلى أن الاستثمار السياحي في مدينة عدن شهد تراجعاً ملحوظاً خلال الفترة 2011-2020 مقارنة بالفترة 2001-2010 بسبب العديد من المعوقات الهيكلية والقانونية والاقتصادية والسياسية وغيرها. وأن مساهمته في اجمالي الاستثمار قد احتلت المرتبة الثانية خلال الفترتين(2001-2005, 2006-2010), وتراجعت إلى المرتبة الثالثة في الفترتين(2011-2015, 2016-2020). وفي ضوء نتائج الدراسة تم وضع عدد من التوصيات أهمها وضع استراتيجية واضحة للاستثمار السياحي, وبذل كافة الجهود لتوفير الاستقرار السياسي والاقتصادي والمالي, والعمل على هيكلة الاقتصاد الوطني لتوفير مناخ استثماري ملائم. This study aims to explore and analyze tourist investment and its contribution to the overall investment compared to other sectors in Aden from 2001-2020, shed light on hindrances to tourist investment and list most significant requirements to improve tourist investment environment. To achieve the above objectives, a descriptive-analytical method was used. The study concludes that tourist investment in Aden has decreased remarkably from 2011-2020 compared to 2001-2010 due to a number of structural, economic, legal, political, etc. obstacles and that its contribution to the total investment in Aden came in second rank in 2001-2005 and 2006-2010 and went down to third rank in 2011-2015 and 2016-2020. In light of the study conclusions, a number of recommendations are proposed including drawing a clear strategy for tourist investment, making utmost efforts to establish political, economic and financial stability, working to restructure national economy to provide favorable investment environment.
مقال